TRANSFORMASI VISUALISASI GAMBAR ILUSTRASI : pada Naskah Jawa Periode 1800-1920, Sebagai Refleksi Gejala Sosial-Budaya Masyarakat Jawa - Nuning Damayanti Adisasmito (Universitas PGRI Adi Buana Surabaya, 2014)
The tradition of writing and drawing illustrations found in old manuscripts in various ethnic In- donesia, especially on Java community. Most Old Javanese manuscript contains illustrations that unique and local characteristics of Javanese art. Illustration of the ancient Javanese manuscripts are well documented and have a varied range of visual form, unique in styling, how to draw, the theme, as well as a visual object. Visual image is an illustration concept frameworks Java community, as well as a reflection of social life - Javanese culture Colonial period. Illustration on Java Script period 1800-1920 as an aesthetic concept attainment the expression symbol of the Java community. The illustrations in old Javanese manuscripts in 1800-1920 showed a correlation sustainability of such visual language in the era of the past to the present and into the characteristics of Java illustration style, which is the development over time. Illustration of the old Javanese manuscript in the year 1800-1920 has changed and developed its visual state as the interaction between the animism in the Pre-Hinduism era, cultural of Hinduism-Budhism, Islamic and Colonialism paradigms. Of all these characteristics into the connecting thread is narrative, symbolic and simplification form of the nature (stylized), two-dimensional shapes and stylized concepts wayang. Keywords: illustration, illustration tradition, colonialism 1800-1920, Java script, stylized